Babad Banjarsari-Based Ludruk Training for Jombang Tourism Village Development - Hidajad Hidajad; Eko Wahyuni Rahayu; Pambudi Handoyo; Arief Sudrajat; Joko Winarko (Abdimas Indonesian Journal, 2026)
Rural tourism development frequently struggles to convert static historical archives into dynamic, community-driven cultural attractions. This community service project aimed to bridge this gap by transforming the local historical chronicle, Babad Desa Banjarsari, into a functional Ludruk performance script to support the development of a signature cultural attraction for Banjarsari Tourism Village in Jombang Regency. Applying an Asset-Based Community Development (ABCD) framework combined with Participatory Action Research (PAR) principles, the intervention engaged 30 local youth, members of the Tourism Awareness Group (Pokdarwis), and cultural elders through a structured four-stage process: narrative asset mapping, script adaptation, intensive performance coaching, and a public showcase evaluation. The project successfully extracted historical nodes from the manuscript into a three-act Ludruk script suitable for modern tourist audiences. Participant evaluations showed marked improvements in traditional acting techniques (an increase of $+2.7$ on a 5-point scale) and vocal projection (kidungan, $+2.2$), while post-performance audience surveys ($n = 50$) demonstrated that $86%$ strongly agreed on the show's viability as a recurring village tourism event. In conclusion, embedding local chronicles into participatory Ludruk training not only revitalizes an endangered regional folk theater among local youth, but also offers a sustainable, community-led framework for heritage-driven rural tourism development.